Efficacy and safety of tenofovir and entecavir in patients with chronic hepatitis B-related cirrhosis: a systematic review and meta-analysis - Lu Cao; Li Li; Lixing Yang; Nan Zhou; Yu Zhang (Frontiers in Pharmacology)
ObjectivesTo systematically evaluate the efficacy and safety of tenofovir and entecavir in chronic hepatitis B-related cirrhosis.MethodsA comprehensive search was conducted in databases including PubMed, Web of Science, Embase and Cochrane Library from the inception until June 2024. Studies on the use of tenofovir and entecavir for chronic hepatitis B-related cirrhosis were collected.ResultsA total of 14 studies involving 14,208 patients were included. The meta-analysis revealed that tenofovir significantly reduced the cumulative incidence of hepatocellular carcinoma and cumulative mortality compared to entecavir in East Asian popupation, while in non East Asian populations, the two groups are roughly equivalent. After 48 weeks, the hepatitis B virus-deoxyribonucleic acid clearance rate in the tenofovir group were comparable to the entecavir group. Both tenofovir and entecavir showed similar effect in reducing the incidence of hepatic encephalopathy. Compared with the entecavir group, patients in the tenofovir group, including tenofovir disoproxil fumarate and tenofovir alafenamide fumarate showed a significant increase in estimated glomerular filtration rate after 48 weeks of treatment.ConclusionCompared to entecavir, tenofovir significantly reduced the cumulative incidence of hepatocellular carcinoma and cumulative mortality in chronic hepatitis B-related cirrhosis in East Asian population. However, both drugs were comparable in terms of hepatitis B virus-deoxyribonucleic acid clearance and hepatic encephalopathy. Tenofovir did not significantly cause renal dysfunction, but instead improved estimated glomerular filtration rate levels compared with entecavir. Randomized controlled trials with larger sample size are still needed for validation.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024588432.